CODE MIXING IN BR LECTURE VIDEO (EPISODE KEEP AWAY DIVISIVENESS) - Yanti, Disnia Fitri; Nofrita, Misra (Jurnal Ilmu Pendidikan Ahlussunnah, 2025)
This study discusses the phenomenon of code mixing in digital platforms such as Youtube. Code mixing is the mixing of two or more languages in one conversation. This study analyzes video content from the Youtube channel Ristawardi Channel. The purpose of this study is as a linguistic strategy for clarity and expression and reflects cultural identity and social dynamics among speakers. Data were found based on observations and listening to video lectures from the Youtube channel Ristawardi Channel. The results of this study found 50 data on code mixing forms consisting of words, phrases, and clauses. The most common form of code mixing found is clauses. The clause form is widely used when mixing Indonesian and Minang languages. The conclusion of this study is to develop a broader understanding of language use in the context of modern communication and the implications of globalization on linguistics.